Human Security dalam Politik Mitigasi Covid-19 di Kota Pangkalpinang - Putri sabilla safira; Ibrahin Ibrahim; Bahjatul Murtasidin (Universitas 17 Agustus 1945 Jakarta, 2023)
Since Covid-19 pandemic expands, and made world in a great global political dynamics. Global political dynamics focussed on treatment and prevention of Covid-19. The changes of regulations that happen periodically in order to find the more suits, efficients and effectives in finding problem solves for Covid-19 pandemic that’s happened currently. Countries are delivered efforts to survive and addapt in the ambience of pandemic Covid-19 era and not that ease. Thus ambience are mainly talk about human security. Furthermore, Covid-19 pandemic being the causes of structural order changes such as society, economic, and politic. Which, the aim of politic mitigation is to ensure the security setability and its human prosperity.